Modeling and assesment of the sports exoprostheses l0ad-bearing capacity - Dolgov Olexander; Chaika Mariia (НТУ "ДП", 2025)
The purpose of the study is to analyze the structural strength of sports exoprostheses of the foot. The stress and strained state analysis of a prosthesis model made of different materials was carried out. The results can be used to improve the designs of sports exoprostheses and increase their strength and reliability.
Keywords: foot exoprosthesis; modeling; stress; stiffness; structural strength.